The Risk of Attention Deficit Hyperactivity Disorder (ADHD) in Preschool Children - Widyastuti; Nurul Hartini; Nur Ainy Fardana Nawangsari (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
ADHD symptoms in preschool children have an impact on social development, especially social competence. ADHD symptoms in preschool children will increase oppositional behavior and behavioral problems with peers, making it difficult for children to make friends and establish healthy relationships. Early detection of ADHD risk is important, but the picture of ADHD risk in preschool children is still not widely known. This study aims to obtain a description of ADHD symptoms in preschool children in East Java. This study used descriptive quantitative research with a sample size of 202 preschool children. The instrument to detect ADHD risk is the Abbreviated Conners Rating Scale (ACRS). Data findings were analyzed using univariate analysis. The results of data analysis showed that 30% (60 out of 202) preschool children had ADHD risk. The most common ADHD symptom is Tirelessness, or excessive activity. These findings suggest that ADHD risk detection needs attention at the preschool level.